Seismic Vulnerability Assessment Using FEMA P-154 and Welded Mesh Reinforcement in Informal Settlements in Peru - Rojas, Axel Williams Chevarría (2025)
The main objective of this study is to evaluate the seismic vulnerability of 30 self-built houses in the Juan Pablo II human settlement in San Juan de Lurigancho, Lima, Peru, which, due to their informal construction and the use of low-quality materials, presenta high risk of seismic events; To do so, the FEMA-P154 methodology will be used, revealing that 31% have a risk of collapse greater than 50%. Likewise, the results of this research will allow us to identify the main structural deficiencies and propose appropriate reinforcement solutions, thus contributing to improving the safety of the inhabitants of the area and reducing human and material losses in the event of an earthquake. This study evaluates the alternative of welded mesh as a reinforcement proposal to improve the seismic behavior of the houses, which will be evaluated through dynamic and pushover analysis, using tools such as AutoCAD and Etabs to perform structural analysis.